An Analysis of Communication and Social Criticism in Emha Ainun Nadjib’s Poem “God Is Already Very Popular” - Muhamad Agung Setiawan; Lakna Tulas’un; Sutinnarto; Najmi Rizki Khairani; Rif’atul Himmah (Perspective Humanities and Social Sciences, 2025)
Poetry is not only an aesthetic medium, but also a means of communication capable of delivering social critique through symbolic language. This study aims to analyze the linguistic style in Emha Ainun Nadjib’s poem “God Is Already Very Popular” and how its stylistic elements construct messages of social and religious criticism. The dynamics of modern religiosity filled with symbolism, fanaticism, and the commodification of faith serve as an essential context reflected in Cak Nun’s work. This research employs a descriptive qualitative method with a stylistic analysis approach. The analysis was conducted through close reading of the poem, classification of stylistic devices, and interpretation of meaning based on the theoretical framework of social criticism and literary communication. The analysis consists of three stages: (1) identifying figures of speech and poetic structures, (2) categorizing linguistic styles related to communicative messages, and (3) interpreting the relationship between stylistic elements and the conveyed social criticism. The findings reveal that irony is used to highlight shallow religious practices, while metaphor and symbolism implicitly yet sharply portray social conditions. Simile is applied to make abstract concepts more communicative and concrete. Overall, the study demonstrates that Cak Nun’s poem represents a form of indirect social critique, as its messages are delivered implicitly through figurative language. Thus, this research emphasizes that poetic language functions as an effective communication instrument in conveying social criticism while encouraging readers’ spiritual reflection.